Penerapan Kinerja dan Kepuasan terhadap Kualitas Kerja di Masa Covid-19 - Faroman Syarief; Faif Yusuf; Kurniawan Prambudi Utomo; Devy Sofyanty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The This research report is to find out how much influence performance and satisfaction have on work quality during the Covid-19 pandemic, Bekasi City Education Office, while this research methodology uses the SPSS Statistics quantitative method by conducting online and offline survey research, and distributing questionnaires directly face to face. limited to respondents as many as 40 respondents while the findings of performance problems and satisfaction with work quality at the Bekasi City Education Office have not been carried out optimally, especially through restrictions on the application of community activities or PPKM in limited face-to-face operations, there are still employees who are late absent, regulations that are not in accordance with the implementation , and employees have not been able to increase satisfaction maximally in their performance, while the results of the study show that performance and satisfaction with work quality show a significant positive relationship for each variable, that performance and satisfaction with Work quality is prioritized in carrying out administrative activities during the Covid-19 pandemic.